2017
DOI: 10.3390/genes8060152
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Profiling of Human Prefrontal Cortex Neurons in Heroin Users Shows Significant Difference between Genomic Contexts of Hyper- and Hypomethylation and a Younger Epigenetic Age

Abstract: We employed Illumina 450 K Infinium microarrays to profile DNA methylation (DNAm) in neuronal nuclei separated by fluorescence-activated sorting from the postmortem orbitofrontal cortex (OFC) of heroin users who died from heroin overdose (N = 37), suicide completers (N = 22) with no evidence of heroin use and from control subjects who did not abuse illicit drugs and died of non-suicide causes (N = 28). We identified 1298 differentially methylated CpG sites (DMSs) between heroin users and controls, and 454 DMSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 98 publications
8
52
0
Order By: Relevance
“…Next, we independently validated our top aging-DMCGs using another public cohort of NeuN-sorted prefrontal cortex brain samples [ 61 ]. From this dataset (GSE98203), we only used healthy, NeuN-positive controls as NeuN-negative data was not available.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we independently validated our top aging-DMCGs using another public cohort of NeuN-sorted prefrontal cortex brain samples [ 61 ]. From this dataset (GSE98203), we only used healthy, NeuN-positive controls as NeuN-negative data was not available.…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic changes in the brain may be highly localized, as studies utilizing whole brain tissue have often reported no significant change in global DNA methylation levels following morphine exposure 19,20 . Targeted approaches have proven more insightful, identifying changes in regions of the brain associated with addiction such as the hippocampus, medial prefrontal cortex and VTA in a rat model of heroin self-administration and reward devaluation 21 and post-mortem orbitofrontal cortex brain tissue from former heroin users 22 .…”
Section: Introductionmentioning
confidence: 99%
“…S12B-C). Using CG dinucleotides that exhibited methylation changes statistically associated with aging neurons from human prefrontal cortex ( 46 ), we found some direct overlap with DRHs and a closer relative distance than random (fig. S12D-E).…”
Section: Main Textmentioning
confidence: 93%